2022
DOI: 10.1021/acsbiomaterials.2c01051
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-Based Supramolecular Hydrogels: From Synthesis and Structural Properties to Biomedical and Tissue Engineering Applications

Abstract: Supramolecular hydrogels are of great interest in tissue scaffolding, diagnostics, and drug delivery due to their biocompatibility and stimuli-responsive properties. In particular, nucleosides are promising candidates as building blocks due to their manifold noncovalent interactions and ease of chemical modification. Significant progress in the field has been made over recent years to allow the use of nucleoside-based supramolecular hydrogels in the biomedical field, namely drug delivery and 3D bioprinting. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…We previously noted that the gelation process is very fast with the K + , providing stronger hydrogels when compared to other metal ions, Ba 2+ , Mn 2+ , Fe 3+ and Ca 2+ . 8 The structures of hydrogels containing Dex decorated with 100% G (DGH1), 50% G (DGH2) and 30% G (DGH3) were confirmed by circular dichroism (CD), FTIR, and X-ray diffraction (XRD) analyses. The CD spectra of all hydrogels exhibited two major peaks, positive at 235 nm and 300 nm and a characteristic negative contribution at 260 nm, which correlates to the distinctive peaks of the G4-stacked structures (Fig.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We previously noted that the gelation process is very fast with the K + , providing stronger hydrogels when compared to other metal ions, Ba 2+ , Mn 2+ , Fe 3+ and Ca 2+ . 8 The structures of hydrogels containing Dex decorated with 100% G (DGH1), 50% G (DGH2) and 30% G (DGH3) were confirmed by circular dichroism (CD), FTIR, and X-ray diffraction (XRD) analyses. The CD spectra of all hydrogels exhibited two major peaks, positive at 235 nm and 300 nm and a characteristic negative contribution at 260 nm, which correlates to the distinctive peaks of the G4-stacked structures (Fig.…”
mentioning
confidence: 95%
“…[1][2][3][4] In particular guanosine, a nucleoside and its analogues able to self-assemble into guanosine-quartets (G4) in the presence of various cations or into linear ribbons, have been extensively exploited for the fabrication of supramolecular gels. [4][5][6][7][8] The internal G4 network formed via H-bonding and metal coordination may be cross-linked via dynamic covalent bonds allowing for the encapsulation of large amounts of water molecules. It offers the entire hydrogel self-healable and injectable properties.…”
mentioning
confidence: 99%
“…In recent years, supramolecular hydrogels have received increasing attention due to their tuneable and reversible character based on small building blocks that link together to form complex networks. Thus, these materials are able to adapt to changing environmental conditions ( Li et al, 2020 ) and can self-heal after experiencing damage ( Godoy-Gallardo et al, 2023 ). Of all the types of supramolecular hydrogels studied that have these properties [e.g., fatty acids ( Nuthanakanti and Srivatsan, 2020 ), sugars ( Goel et al, 2021 ), cholesterol ( Zhang et al, 2021 ), amino acids ( Xie et al, 2020 ), peptides ( Falcone et al, 2020 )] and silk fibroin ( Yao et al, 2022 ; Zou et al, 2022 ), nucleoside-based hydrogels appear most promising for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, guanosine (G) and its analogues are conjugated with low- and high-molecular-weight molecules to enhance the self-assembly driven hydrogelation, increase the lifetime stability, and assign dynamic multifunctional properties to the developed G-quadruplex supramolecular structures. In particular, boronic acid is a highly versatile and one of the most commonly used building blocks for multicomponent self-assembly due to its ability to bind molecules containing diol groups, namely cis -1,2-diols, ,,, such as G. Thereby, it enables the formation of dynamic and reversible cyclic boronate ester bonds-mediated G-quadruplex hydrogels denoting stimuli-responsive behavior, self-healing, injectable, or shape memory properties. ,,, Recently, Biswas et al engineered a dynamic, stimuli-sensitive polyethylene (PEG)-functionalized G-quadruplex hydrogel for sustained doxorubicin release using 2-formylphenylboronic acid (2-FPBA) and G . Moreover, Tanaka et al reported the preparation of biodegradable and self-healable supramolecular G-quadruplex hydrogels by directly and symmetrically coupling deoxyguanosine monomers to the ends of the PEG chains, in the presence of K + or Na + , holding great promise to be used as drug carriers .…”
Section: Introductionmentioning
confidence: 99%